Aggressiveness in Children of Eight Years from Two-Parent and Single-Parent Families - Светлана Валерьевна Бедрединова; Анна Ивановна Тащёва; Людмила Николаевна Малышко (Rossijskij psihologičeskij žurnal., 2015)
In the article the authors oXer the comparative analysis of aggression in modern girls and boys. There is quite a lot of research of aggression in domestic and foreign psychology. However, the absolute majority of these works concern adults and children of older age groups (e.7g. adolescents); almost all the studies on children of eight years are carried out by psychologists of our country from the middle to the end of the 20th century. There are virtually no studies concerning features of aggressiveness in modern children of the analyzed age. The authors could not Ynd empirical studies on gender diXerences in the manifestation of aggression in children of this age, connection of one of the most important and interesting psychological phenomena with other psychological characteristics of children of eight years. Respondents at the age of eight7– pupils of the Yrst form of secondary schools7– were the object of the study. Methodological tools of research included tests of S.7Rosenzweig and R.7Kettell (CPQ 12), “Nonexistent Animal” technique, A.7I.7Tashcheva’s questionnaire “Attribute Support Communication” (“ASC”). The main results of the study have made it possible to demonstrate the typical behaviors of children of eight years in frustrating situations, common gender features of children’s reactions to conZict regardless of their sex; speciYc reactions in conZict situations of children with high aggressiveness and children with “normative” and low aggressiveness. The obtained results can be useful to psychologists, teachers and parents for eXective understanding and interaction with children of eight years, for creating a7psychological support program for reducing the level of aggressiveness in boys and girls of the studied age.